2010
DOI: 10.1007/s10709-010-9493-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and molecular composition of heterochromatin in the holocentric chromosomes of the aphid Rhopalosiphum padi (Hemiptera: Aphididae)

Abstract: In order to study the structure of holocentric chromosomes in aphids, the localization and the composition of Rhopalosiphum padi heterochromatin and rDNA genes have been evaluated at cytogenetic and molecular level. In particular, heterochromatin resulted located on all the chromosomes both in intercalary and telomeric positions. Moreover, enzymatic digestion of R. padi genome put in evidence a DraI satellite DNA which has been isolated, cloned and sequenced. FISH experiments showed that this satellite DNA clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The few studies carried out to date on satDNA sequences in organisms possessing holocentric chromosomes have mostly focused on nematodes (Roth, ; Collet & Westerman, ; Naclerio et al , ; Castagnone‐Sereno et al , 1998 a , b ). Among aphids, satellite DNAs have been isolated in five aphid species only: one in Megoura viciae (Bizzaro, Manicardi & Bianchi, ), one in Rhopalosiphon padi (Linnaeus) (Monti, Manicardi & Mandrioli, ), two in M. persicae (Spence et al , ; Mandrioli et al , 1999 a ), two in Amphorophora tuberculata (Spence & Blackman, ) and four in Aphis nerii (Mandrioli et al , )…”
Section: Distribution Of Repeated Dna In the Aphid Chromosomesmentioning
confidence: 99%
See 3 more Smart Citations
“…The few studies carried out to date on satDNA sequences in organisms possessing holocentric chromosomes have mostly focused on nematodes (Roth, ; Collet & Westerman, ; Naclerio et al , ; Castagnone‐Sereno et al , 1998 a , b ). Among aphids, satellite DNAs have been isolated in five aphid species only: one in Megoura viciae (Bizzaro, Manicardi & Bianchi, ), one in Rhopalosiphon padi (Linnaeus) (Monti, Manicardi & Mandrioli, ), two in M. persicae (Spence et al , ; Mandrioli et al , 1999 a ), two in Amphorophora tuberculata (Spence & Blackman, ) and four in Aphis nerii (Mandrioli et al , )…”
Section: Distribution Of Repeated Dna In the Aphid Chromosomesmentioning
confidence: 99%
“…Molecular analyses of these aphid satDNAs have shown that their consensus sequences are variable in length from 100 to 600 bp, and that none of them possesses significant direct or inverted repeats (Bizzaro et al , ; Spence et al , ; Monti et al , ; Mandrioli et al , ).…”
Section: Distribution Of Repeated Dna In the Aphid Chromosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…72 This supports the opinion expressed above in relation to the Commission's endorsement of pollution abatement as an efficiency gain on par with traditional economic efficiencies in the Article 81(3) EC inquiry. 73 Secondly, the Commission explicitly acknowledges that the collective environmental benefits generated by the agreement would be sufficient, without more, to satisfy the second positive criterion of Article 81(3) EC. Some commentators have criticised this approach for extending the ambit of Article 81(3) EC from a provision essentially concerned with consumer benefits to one which addresses total welfare.…”
Section: Commission Decisional Practice: Post-amsterdammentioning
confidence: 99%